Nachwuchsleistungssport in den NRW-Sportschulen - Talentsichtung unter Berücksichtigung sportartübergreifender, sportartspezifischer und sportpsychologischer Testverfahren - Roth, A.; Moll, C.; Seidel, I.; Bös, K. (Leipziger Sportwissenschaftliche Beiträge, 2017)
In this paper, three questions are discussed. At first (question 1) the talent promotion concept is described at the 18 Sport Schools in North Rhine Westfalia in more details. Question 2 deals with the diagnostic procedures used in the selection and promotion process. Based on two years of investigation in national and international talent literature and supported by numerous experts of science and practice, Motor Test 1 (MT1) and Motor Test 2 (MT2) have been developed for talent search at the 18 Sport Schools. Altogether up to the school year 2015/16 approx. 9,500 children in class 4 and approx. 1,800 children in class 7 were tested. In the third chapter (question 3) results are reported. The examination of MT2 shows, that the calculated reliability coefficients of tests in MT2-A, MT2-B Swimming and MT2-B Athletics strew from 0.67 to 0.98. A further presented study includes the evaluation of standard values of the Sport Orientation Questionaire (SOQ). The results indicate that the SOQ differentiates gender-specific and can be used succesfully in the selection talks. The common long-term goal of all participants is to develop existing institutions and networks for the promotion of talent, including the integrated system school-competive sports, in order to enable a successful school carrer in addition to sporting development.